Pengaruh Kompensasi, Rekrutmen, dan Reputasi Perusahaan terhadap Minat Melamar Pekerjaan Generasi Z di PT Kindo Dwi Persada - Nasywa Aulia; Dewi Andriani; Vera Firdaus (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of compensation, recruitment, and company reputation on Generation Z's interest in applying for jobs at PT. Kindo Dwi Persada. The population was students of Muhammadiyah University of Sidoarjo with the Gen Z category aged 18-25 years. A sample of 101 participants was obtained through purposive sampling. Data were collected using a Likert scale Google Form online questionnaire and analyzed using SEM-PLS. The results of this study revealed that the variables of compensation, recruitment, and company reputation had a positive and significant effect on Gen Z's interest in applying for jobs at PT Kindo Dwi Persada.